Binding Constants Determination of Ofloxacin and Ornidazole Enantiomers with Sulfated β-Cyclodextrin as Single Ligand by Capillary Electrophoresis using Three Different Linear Plotting Methods - M. Al Azzam, Khaldun (Asian Journal of Chemistry, 2021)
The aim of this research is to use capillary electrophoresis to establish/determine the binding constants for ofloxacin and ornidazole enantiomers with the negatively charged chiral selector sulfated-β-cyclodextrin (S-β-CD). Using electrophoretic mobility values of ofloxacin and ornidazole enantiomers at various concentrations of S-β-CD used in the context of background electrolyte (BGE), binding constants were calculated using three separate linearization plots, namely double-reciprocal, X-reciprocal and Y-reciprocal. The R-ofloxacin enantiomer-S-β-CD complex had the highest inclusion affinity of the ofloxacin and ornidazole enantiomers, which matched with previously reported estimation. Every enantiomer-S-β-CD complex’s binding constants, as well as thermodynamic binding parameters, were calculated at different temperatures. The host-guest binding constants using double reciprocal fit showed greater linearity (R2 > 0.99) at all temperature ranges measured (15-30 ºC) as compared to the other two fit approaches. The thermodynamic complexation parameters were found to be dependent on the temperature of the enantiomers, as seen by the linear van’t Hoff (15-30 ºC) plot.